The relationship between communication skills of nursing students and their attitudes towards teamwork: A case from Turkey - Güneşer, Ramazan; Kirimlioğlu, Nurdan (Acta Bioethica, 2025)
Effective communication and teamwork have a critical role in nursing. This study aims to determine the relationship between nursing students' communication skills and attitudes toward teamwork (n=334). The communication skills (104.82±11.47) and teamwork attitudes (120.41±13.28) scores of the students were found to be at a high level. The total scores of the communication skills scale (p=0.007) and the scores of the communication principles and basic skills (p=0.001), effective listening, and nonverbal communication (p=0.008) sub-dimensions of the students who received training on teamwork were higher than those of the students who did not receive training. The total scores of the teamwork attitudes questionnaire (p=0.024) and the sub-dimension scores of team structure (p=0.020) and situation monitoring (p=0.048) of the students who received training on teamwork were higher than those who did not receive training. It was found that the scores of male students in the mutual support sub-dimension of the teamwork attitudes questionnaire were significantly higher (p=0.026) compared to female students. There was a moderate positive correlation between the scores of communication skills and teamwork attitudes (r= 0.467, p<0.001). Nursing students had high communication skills and attitudes toward teamwork, and the relationship between them was significant.